Preparation of low calorie and shelf‐life extended yogurt by mixing wood apple powder in the formulation. Issue 12 (3rd November 2019) - Parvin, Ishita; Haque, M. Amdadul; Akter, Fatema; Zakaria, M.; Baqui, M. A.
Abstract: The study was designed to develop a low calorie and shelf‐life extended fruit yogurt mixed with wood apple powder. The fruit powder was supplemented at different levels in order to recommend an appropriate formulation. From the proximate analyses, it was found that the major components such as protein, fat, and moisture contents varied slightly in the yogurt samples. However, the plain yogurt was found to contain a higher amount of carbohydrate (18.83%) than that of wood apple powder yogurt (12.72%). From the organoleptic responses, the yogurt sample containing 6% fruit powder and 20% table sugar secured the highest score in color, texture, and taste. A fruit mixed yogurt sample was prepared with as less as 30% low calorie content than the plain one. The fruit powder yogurts were found to have 5 to 6 days more shelf‐life than that of the plain yogurt at refrigeration temperature (7°C). Practical applications: The food items with low sugar content have proved to be very helpful in maintaining the soundness of health. The current study shows that only an appropriate formulation can provide healthier food, ensuring acceptable qualities. The study demonstrates how the natural fruit sugar and fruit acid contribute in preparing low calorie as well as shelf‐life extended yogurt. The laboratory investigations have suggested the appropriate formulation of wood apple yogurt with pros and cons regarding nutritive and organoleptic qualities. The findings of the study are highly expected to be helpful for the bakery and confectionary products manufacturers to prepare the yogurts with low calorie content and naturally enhanced shelf‐life.